Governance of MSMEs Tourism Based on Local Wisdom that is Competitive and Sustainable in Herbal Tourism Destinations Tawangmangu - Faskahariyanto, Kristian; Edy, Irwan Christanto; Adinugroho, Suryo (International Journal of Business, Economics, and Social Development, 2023)
This research aims to conduct in-depth research to find out the governance model of local wisdom-based MSMEs that are sustainably competitive, especially in facing the crisis period, after the Covid-19 pandemic. This research uses variables and a map of the relationship between variables on the impact of sustainable competitive tourist destinations on the welfare of tourism MSME actors. This research was conducted on MSME players in herbal tourism destinations, especially the Tawangmangu destination, Karanganyar Regency, Central Java Province, Indonesia. The approach used is a qualitative method. In collecting data using in-depth interviews, FGDs, observation, study of related documents, and surveys. The determination of the research sample uses purposive sampling technique which is adjusted to the criteria. It is expected that this research can find out the governance of MSMEs that are sustainably competitive in the midst of a crisis and find out the supporting and inhibiting factors for the governance of tourism MSMEs that are sustainably competitive in tourism destinations, as well as preparing tourism MSMEs towards a global market (Go International) that is sustainably competitive and has an impact on the welfare of MSME actors in Tawangmangu herbal tourism destinations.